The role of cerebellar GABA in visuomotor adaptation - Nettekoven, C (2020)
In daily life we must constantly adapt our movements to changes in the environment or changes in our body. Adaptation is a fundamental property of the central nervous system and involves plastic changes across a network of brain regions, in particular in the cerebellum. These changes likely involve the major inhibitory neurotransmitter GABA. How cerebellar GABA changes during adaptation and how these changes are linked to behaviour is currently not well understood. By combining brain imaging (Magnetic Resonance Spectroscopy and Magnetic Resonance Imaging) and brain stimulation (transcranial direct current stimulation; tDCS) with computational modelling of behaviour, this thesis investigates the relationship between GABA, plasticity and motor adaptation.